Uji Aktivitas Sitotoksik Ekstrak dan Fraksi dari Spon Laut Petrosia Sp dengan Metoda Brine Shrimp Lethality Test - Krisyanella, Krisyanella; Handayani, Dian; unance, Lendra Y (Jurnal Sains dan Teknologi Farmasi, 2011)
Determination of cytotoxic activity of the extract and fraction of marine sponge Petrosia sp suing Brine Shrimp Lethality Test has been done. The Cytotoxic activity analysis was done toward methanol extract first, then continued to n-hexane, ethyl acetate and buthanol fractions respectively. The LC50 values were 70.736 ppm, 269.153 ppm, 197.38 ppm and 70.667 ppm respectively. Results showed that the extract and fraction of Petrosia sp potentially has cytotoxic activity whereas buthanol fraction has the higest citotoxic activity among at all. Phytochemistry screening for buthanol fraction contained terpenoid, steroid and saponin.